Delivery of basic health services by the local government unit in the fourth district of Pangasinan - Delos Santos, Iolie M. (Metro Dagupan College : [s.n.], 2017)
The study assessed the delivery of basic health services in the fourth district of Pangasinan in order to propose measures to improve the provision of healthcare services in the devolved set-up. This study employed the descriptive method of investigation, which utilized the survey questionnaire as method of gathering data. Casual interview were used by the researcher to gather additional information from the RHU personnel. The health service providers in the fourth district of Pangasinan comprises of the following: 53 personel from Mangaldan RHU, 48 from San Jacinto RHU; 45 from Fabian RHU; and from Manaoag RHU. These RHU personnel comprise of medical doctors, public health nurses, midwives, sanitary inspectors, dentist and dental aids, barangay health workers, and municipal health employees.
Bibliography: pages 148-150.
CHED-La Union
Keywords: Health care; Health services